а
13(x - 2)+213(x+1)= 613 ;
Б) 25 (х + 2) + 4/6 = 35 (2x + 2/2) - 2/3x;
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
a) 13(x-2)+213(x+1)=613
13x-26+213x+213=613
226x+187=613
226x=613-187
226x=426
x=426/226
b)25(x+2)+4/6=35(2x+2/2)-2/3 x
25x+50+4/6=35(2x+1)- 2/3 x
25x+152/3=70x-35- 2/3 x
75x+152=210x+105-2x
75x+152=208x+105
75x-208x=105-152
-133x=-47
x=47/133
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Chimie,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă